Investigation Study of the Challenges in Green Procurement Implementation in Construction Projects in UAE - Muataz Hazza Al Hazza; Maktoom Muqtadar; Khaled El Salamony; Islam F. Bourini; Ahmad Sakhrieh; Mohammed Alnahhal (Civil Engineering Journal, 2023)
The global construction industry is responsible for significant environmental and societal effects. Some researchers claim that it accounts for 35% of global gas emissions. One of the solutions is to practice green supply chain management. Part of this is Green Procurement (GP) to conserve energy and money. However, challenges in implementing green procurement in the construction industry are rising. This research aims to identify the most significant challenges when implementing green procurement (GP) in construction projects in the UAE. A comprehensive article review was conducted to determine the critical obstacles highlighted by different researchers. These challenges were prioritized using the analytical hierarchy process (AHP) method, and then recommendations on best practices to overcome these challenges were proposed. The results show that the lack of top management commitment is the biggest challenge when implementing green procurement in the construction industry in the UAE, with a priority value of 0.331, followed by a lack of knowledge, with a value of 0.2748. In contrast, lack of awareness is the lowest-ranked factor, with a value of 0.103. Doi: 10.28991/CEJ-2023-09-04-06 Full Text: PDF